2009
DOI: 10.1111/j.1365-2958.2009.06630.x
|View full text |Cite
|
Sign up to set email alerts
|

CtrA response regulator binding to the Caulobacter chromosome replication origin is required during nutrient and antibiotic stress as well as during cell cycle progression

Abstract: SummaryThe Caulobacter crescentus chromosome replication origin (Cori ) has five binding sites for CtrA, an OmpR/ PhoB family 'response regulator'. CtrA is degraded in replicating 'stalked' cells but is abundant in the nonreplicating 'swarmer' cells, where it was proposed to repress replication by binding to Cori. We systematically mutated all Cori CtrA binding sites, and examined their consequences in the contexts of autonomous Cori-plasmid replication and in the natural chromosome locus. Remarkably, the C. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…In addition to this dimorphic control, C. crescentus chromosome replication occurs once and only once per cell division cycle (18). However, CtrA activity does not block extra rounds of chromosome replication prior to cell division (16,19).Escherichia coli uses at least three mechanisms to block extra rounds of chromosome replication. As reviewed by Katayama and coworkers (20), E. coli possesses two mechanisms that restrict DnaA binding to the origin of replication (oriC) and one mechanism, termed RIDA (regulatory inactivation of DnaA), that inactivates DnaA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this dimorphic control, C. crescentus chromosome replication occurs once and only once per cell division cycle (18). However, CtrA activity does not block extra rounds of chromosome replication prior to cell division (16,19).Escherichia coli uses at least three mechanisms to block extra rounds of chromosome replication. As reviewed by Katayama and coworkers (20), E. coli possesses two mechanisms that restrict DnaA binding to the origin of replication (oriC) and one mechanism, termed RIDA (regulatory inactivation of DnaA), that inactivates DnaA.…”
mentioning
confidence: 99%
“…Chromosome replication is coupled to this dimorphic cell division since only the stalked cells initiate chromosome replication, and the swarmer cells differentiate into stalked cells before they replicate their chromosomes (9-13). CtrA is a global response regulator protein that binds to and represses the C. crescentus origin of chromosome replication in the swarmer cells (10,(14)(15)(16). Competitive binding between CtrA and DnaA is a key mechanism of replication control that blocks replication in swarmer cells while allowing replication in the stalked cells (10,17).…”
mentioning
confidence: 99%
“…Even more puzzling is that all the CtrA binding sites in the Cori region can be mutated together without leading to additional rounds of replication in a single cycle (10). Clearly there are other mechanisms, yet to be discovered, at work.…”
Section: Regulation Of Dna Replication and Methylation Machinerymentioning
confidence: 99%
“…Thus, the phosphorylated form of CtrA (CtrAϳP) represents its active form. In swarmer cells, CtrA is active and binds to the five sites (termed A to E) in the Cori region, thereby repressing replication initiation (10,199). Specifically, the A and B sites work cooperatively to block P s activity, site C overlaps the IHF binding site, and site E overlaps a DnaA box (199,220,221).…”
Section: The Origin Of Replicationmentioning
confidence: 99%
“…The interaction of master regulators with their targets presumably interferes with the formation of functional orisomes, thereby preventing replication initiation. Indeed, in vivo experiments demonstrated that B. subtilis, C. crescentus, and S. coelicolor with oriC regions lacking the Spo0A-, CtrA-, and AdpA-binding sequences, respectively, exhibited chromosome overreplication (15,76,85). The master regulators can probably displace DnaA from oriC (as shown for CtrA [77]) or prevent DnaA from oligomerizing at oriC and thus block the formation of a functional orisome by limiting DnaA access to the replication origin.…”
Section: Master Regulators Inhibit Replication Initiation During the mentioning
confidence: 99%